JURIDICAL REVIEW LARGE-SCALE SOCIAL RESTRICTIONS IMPLEMENTED BY LOCAL GOVERMENTS - Nur Fasha, Moch Gandi; Diamantina, Amalia (JCH (Jurnal Cendekia Hukum), 2023)
This research discusses the policy guidelines for implementing PSBB, which is one of the models used by the Government in handling Covid-19. The focus is on the legal issues related to the process of determining PSBB at the regional level. The paper uses a normative juridical approach to examine the proposed PSBB policy by the Local Government and its legal implications. The research finds that the proposed PSBB policy has limited the Local Government's ability to set PSBB at the regional level. The legal implications of imposing large-scale social restrictions at the regional level have resulted in a failure to realize the legal benefits of treating the Covid-19 pandemic as an emergency. The direction and legal implications of the proposed PSBB policy are discussed in detail in this paper.